First things first : hip-hop ladies who changed the game - Simmons, Nadirah (Twelve, an imprint of Grand Central Publishing, 2024)
"First Things First, hip-hop is not just the music, and women have played a big role in shaping the way it looks today. First Things First takes readers on a journey through some notable firsts by women in hip-hop history and their importance. Factual firsts like Queen Latifah becoming the first rapper to get a star on the Hollywood Walk of Fame, Lauryn Hill making history as the first rapper to win the coveted Album of the Year Award at the GRAMMYs, April Walker being the first woman to dominate in the hip-hop fashion game, and Da Brat being the first solo woman rapper to have an album go platinum, and metaphorical firsts like Missy Elliott being the first woman rapper to go to the future. Altogether, First Things First is a celebration of the achievements of women in hip-hop who broke down barriers and broke the mold. So the next time someone doesn't have their facts straight on the ladies in hip-hop, you can hit them with "first things first"..."--